EFFECTIVE WAYS AND TECHNIQUES OF TEACHING FOREIGN LANGUAGES TO YOUNG LEARNERS (International journal of artificial intelligence, 2025)
This paper discusses the effective ways and techniques of teaching foreign languages to young learners. It emphasizes the importance of adapting teaching methods to the developmental stages of children and highlights various strategies to enhance language acquisition. The research explores communicative approaches, play-based learning, and the integration of technology in language instruction. By examining the cognitive and social needs of young learners, the paper offers insights into how educators can create engaging and effective learning environments. The findings demonstrate that a combination of interactive, dynamic, and context-driven methods significantly improves language learning outcomes for children.